DEVELOPING REGISTRATION MODULE IN HEALTH INFORMATION SYSTEMS USING THE DESIGN THINKING METHOD - Ratu Amalia Primadiningsih; Rahmat Izwan Heroza (Jurnal Riset Informatika, 2022)
In applications, usability is an essential factor that shows the user experience whether the application is easy to use and fits its function or not. For this reason, this study aims to determine the usability of the registration module on the Khanza Hospital Management Information System (SIMRS) used by RSUD Banyuasin employees and to find out the difficulties faced, needs, and desires of RSUD Banyuasin employees as users of SIMRS Khanza. This research is helpful for the agency as a subject of application evaluation and helps discover what opportunities can be applied to overcome user difficulties. The approach used is Design Thinking. Meanwhile, the usability measurement uses the System Usability Scale (SUS) involving five respondents. The initial results of measuring the usability of SIMRS Khanza obtained were 26 with a poor rating. In addition, the interview results show that users have difficulty learning the application, the features and fields are too many, and there is a redundancy of patient data. Based on these findings, the researcher recommends a solution design with a High Fidelity Prototype (Hi-fi) with a final value of SUS 87. With the implementation of this research recommendation, it is hoped that it can help the performance of RSUD Banyuasin with an application design that is easy to understand and supports the creation of accurate and consistent data.